Pengaruh Variabel ROA, ROE, DER, EPS dan PER terhadap Return Saham Perusahaan Non Bank LQ45 Periode 2010-2012 - Cerlienia Juwita; Juni Herawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
In the era of globalization, many people who want a investment for profit. Investors in this paasti always do a lot of consideration before making the investment. Function of this study is to analyze the influence of Return on Assets, Return on Equity, Debt Equity Ratio, Earnings per Share and Price Earning Ratio of Stock Return in non bank company's annual report LQ45 in Indonesia. The population in this study is consistent 45 companies listed in Indonesia Stock Exchange LQ45 index (BEI) in the study period from 2010 to 2012 and the sample consists of 10 firms meet the criteria established by purposive sampling. Analysis of the data used is multiple linear regression. Results of this study showed that the ratio of Return on Assets, Return on Equity, Earnings per Share and Price Earning Ratio significantly influence the company's stock returns. Debt Equity Ratio Meanwhile no significant effect on the company stock returns. Keywords: Profitability, Solvency, Market Value and Stock Return